PEMBERATAN PIDANA DALAM TINDAK PIDANA PEMBALAKAN LIAR KETIKA TERJADI BENCANA - Surasto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study aims to examine and analyze the need for weighting of criminal threats in the crime of illegal logging in the event of a disaster. The legal materials used are primary legal materials collected by taking an inventory of the laws and regulations that are closely related to forestry crimes. Research Results Weighting criminal threats to illegal logging crimes during a disaster is needed on the basis that the general provisions of policies on illegal logging do not yet contain provisions for weighting criminal threats, the impact of repeated illegal logging needs to be the attention of policy makers, and the importance of weighting the criminal threat of illegal logging during disasters , because the deforestation rate is mostly illegal logging, and in order to increase the culture of obedience of business actors and provide a deterrent effect for criminals as well as future criminal policies on illegal logging crimes in the event of a disaster on the consideration that illegal logging is a multi-effect crime. By analogy with the criminal penalties in the regulation of criminal acts of corruption in the form of weighting criminal threats if corruption is carried out on disaster management funds, then in the forestry sector against illegal logging crimes, a policy of criminal penalties against illegal logging carried out during disasters is also formulated.